Modelling the mechanical characteristics and on-snow performance of snowboards - Brennan, S. M.; Kollar, L. P.; Springer, G. S. (Sports Engineering, 2003)
Models were developed for calculating the mechanical characteristics and the on-snow performance of snowboards.The snowboards are constructed of layers of materials which may include wood, foam, honeycomb, fibre-reinforced composites and polymeric materials.The models pertaining to the mechanical characteristics provide the bending and torsional stiffnesses, the flex and the twist.A computer code (Snowboard-MECH) was written which yields numerical values for these characteristics.The model for on-snow performance simulates the travel of a snowboarder of given height, weight and skill level, down an S-shaped course.A second computer code (Snowboard-TURN) was written in support of this model; this calculates the time it takes the snowboarder to complete the course.The two computer codes were verified by comparing their outputs with laboratory data and with data generated by a snowboarder completing a prescribed S-shaped course.The results generated by the models and the data are in agreement, lending support to the models and the corresponding computer codes.A procedure is described by which the computer codes developed in this study can be utilized in the design of snowboards.